Предмет: Алгебра,
автор: xde90
Упростите выражение (у+6)^2-(у+1)(у-2)
Ответы
Автор ответа:
0
Ответ:
(
y
2
−9
6
+
3−y
1
)∗
5
y
2
+6y+9
=(
(y−3)(y+3)
6
−
y−3
1
)∗
5
(y+3)
2
=
=
(y−3)(y+3)
6−y−3
∗
5
(y+3)
2
=
(y−3)(y+3)5
(3−y)(y+3)
2
=
(y−3)5
−(y−3)(y+3)
=−
5
y+3
zlataburmistrova3:
в строчку надр писать у меня так отправилось
Автор ответа:
0
Всё решение на фото
Приложения:
Похожие вопросы
Предмет: Русский язык,
автор: 158marinanaran
Предмет: Русский язык,
автор: ilnaz041
Предмет: Українська мова,
автор: ire2
Предмет: Математика,
автор: Аноним
Предмет: Математика,
автор: ася0910